2019
DOI: 10.31234/osf.io/2xm9w
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Retro-cueing in multi-attribute choices: The influence of memory availability on strategy selection and attribute weights

Abstract: Decision making in multi-attribute choices is adapted to the structure of the task. The availability of information in memory was recently proposed as driving this adaptation. We studied this hypothesis in the context of purchase decisions by using eye tracking and computational modelling in controlled lab experiments. We particularly manipulated memory availability through a retro-cue, thereby highlighting one attribute in a multi-attribute choice task in which participants decided among products (movies, boo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
(62 reference statements)
0
2
0
Order By: Relevance
“…In studies on task instructions, participants receive instructions concerning a specific decision goal, and with that, what is it relevant to gaze at. For instance, the participants may be instructed on the validity of stimulus attributes (Krefeld-Schwalb & Rosner, 2019) or infer the level of validity themselves (Bialkova et al, 2014). In preferential viewing studies, the relevance should be equal to the subjective preferences.…”
Section: Cognitive Factors Have Effect Sizes Similar In Magnitude To ...mentioning
confidence: 99%
See 1 more Smart Citation
“…In studies on task instructions, participants receive instructions concerning a specific decision goal, and with that, what is it relevant to gaze at. For instance, the participants may be instructed on the validity of stimulus attributes (Krefeld-Schwalb & Rosner, 2019) or infer the level of validity themselves (Bialkova et al, 2014). In preferential viewing studies, the relevance should be equal to the subjective preferences.…”
Section: Cognitive Factors Have Effect Sizes Similar In Magnitude To ...mentioning
confidence: 99%
“…Although these models all specify different information search processes, they make similar implicit assumptions about the nature of visual search and hence attention in decision making. The models assume that information search is determined by a search rule inherent to the decision process, for example, attend to alternatives one at a time until a satisfactory alternative is found (Stüttgen et al, 2012), or attend to information cues in order of their predefined validity until a cue is found that identifies the best alternative (Krefeld-Schwalb & Rosner, 2019). Overt attention is sometimes used to test such process assumptions (Glöckner & Herbold, 2011).…”
mentioning
confidence: 99%